2019
DOI: 10.1159/000503456
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoids Identification in Lung Tissues of Young Cannabis Smokers Operated for Primary Spontaneous Pneumothorax and Correlation with Pathologic Findings

Abstract: <b><i>Background:</i></b> Several studies suggested the association between tobacco and cannabis smoking and the risk of primary spontaneous pneumothorax (PSP), but none demonstrated cannabinoids in human lung tissues. <b><i>Objectives:</i></b> The aim of this study was to identify cannabinoids in lung specimens of young cannabis smokers, operated for PSP, and investigate on their pathologic findings, to determine the role of cannabis in PSP pathogenesis. <b&g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Increasing evidence supports the association of marijuana smoking with bullous emphysema and spontaneous pneumothorax. A prospective study supports the correlation between marijuana abuse and primary spontaneous pneumothorax [10]. A case-controlled study by Stefani et al revealed that cannabis smokers are at significant risk of developing bullous lung disease and have a higher incidence of tension pneumothorax compared to both tobacco smokers and nonsmokers [9].…”
Section: Discussionmentioning
confidence: 76%
“…Increasing evidence supports the association of marijuana smoking with bullous emphysema and spontaneous pneumothorax. A prospective study supports the correlation between marijuana abuse and primary spontaneous pneumothorax [10]. A case-controlled study by Stefani et al revealed that cannabis smokers are at significant risk of developing bullous lung disease and have a higher incidence of tension pneumothorax compared to both tobacco smokers and nonsmokers [9].…”
Section: Discussionmentioning
confidence: 76%
“…These features suggest a co-carcinogen role for cannabis smoke, which contains a greater quantity than tobacco of polycyclic aromatic hydrocarbons and tar particles [4]. Moreover, the presence of cannabinoids and pathologic alterations have been demonstrated in the lung apex of young cannabis smokers with pneumothorax [15]. In our clinical experience, tumours in the CTS group are frequently diagnosed at an advanced stage.…”
mentioning
confidence: 80%
“…This condition usually occurs in young people, although there are more elderly patients with pneumothorax. With the maturity of rapid rehabilitation and the accumulation of minimally invasive surgical techniques in recent years, lung surgery has entered the era of minimally invasive surgery represented by thoracoscopy [8] . At present, the approaches of thoracoscopic bullectomy include the classic 3-4-hole VATS, two-hole VATS, and single-hole VATS [9,10] .…”
Section: Discussionmentioning
confidence: 99%